Współczesne sposoby motywowania i ich rola w kształtowaniu aktywności pracowników: Modern methods of motivation and their role in shaping the activity of workers - Cołoś, Ilona (Management and Administration Journal, 2021)
The most important task HR managers have to accomplish, regardless of the type of employees they work with; for example, manufacturing workers, dealers, sellers, TV reporters, is to bring out the most precious resources they have such as knowledge, skills, creativity, commitment and flexibility; more generally, to bring out their intellectual value in order to increase the value of the company. In order to carry out this task, they use psychological motivation techniques, which have been evolving over the years. In this article is presented some of the most common methods used to rise the commitment of ours employees are presented.